2019
DOI: 10.1016/s1470-2045(19)30506-6
|View full text |Cite
|
Sign up to set email alerts
|

Levofloxacin prophylaxis in patients with newly diagnosed myeloma (TEAMM): a multicentre, double-blind, placebo-controlled, randomised, phase 3 trial

Abstract: Background Myeloma causes profound immunodeficiency and recurrent, serious infections. Around 5500 new cases of myeloma are diagnosed per year in the UK, and a quarter of patients will have a serious infection within 3 months of diagnosis. We aimed to assess whether patients newly diagnosed with myeloma benefit from antibiotic prophylaxis to prevent infection, and to investigate the effect on antibiotic-resistant organism carriage and health care-associated infections in patients with newly diagnosed myeloma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
120
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(125 citation statements)
references
References 28 publications
2
120
0
3
Order By: Relevance
“…Two studies reported the incidence of severe infections, 7,8 whereas one study did not report on the incidence of severe infections, instead reporting on febrile vs non-febrile infections, and episodes of severe sepsis. 9 The incidence of severe infection, defined as a Grade III or Grade IV infection including hospitalization, was numerically lower for the patients that received antibiotics vs those that did not; however, this did not reach statistical significance (8.0% vs 14.8%, RR: 0.57, 95% CI 0.30-1.06, P = .08, I 2 = 0%) ( Figure 3).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Two studies reported the incidence of severe infections, 7,8 whereas one study did not report on the incidence of severe infections, instead reporting on febrile vs non-febrile infections, and episodes of severe sepsis. 9 The incidence of severe infection, defined as a Grade III or Grade IV infection including hospitalization, was numerically lower for the patients that received antibiotics vs those that did not; however, this did not reach statistical significance (8.0% vs 14.8%, RR: 0.57, 95% CI 0.30-1.06, P = .08, I 2 = 0%) ( Figure 3).…”
Section: Discussionmentioning
confidence: 96%
“…One study reported a lower incidence of hospitalization in the intervention group vs control group (88 vs 114 events, P value not provided). 9 The sensitivity analysis for each outcome was consistent when alternate model using fixed effect and Mantel-Haenszel method was applied. al was either an immunomodulatory drug (thalidomide in 43%, lenalidomide in 15%) or proteasome-based regimen (bortezomib in 31%).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We recommend prophylaxis against pneumocystis jiroveci for all patients on dexamethasone. We also recommend levofloxacin daily for the first two cycles in all patients with newly diagnosed MM 28 .…”
Section: Dosage and Supportive Care Considerationsmentioning
confidence: 99%
“…Susceptibility to infection is primarily the consequence of acquired tumor-related deficiency of both humoral and cellular immunity. The publication by Drayson et al [6] in Lancet Oncology is a welcomed focus on supportive care in myeloma. They present the findings that showed that 12 weeks of fixed-duration levofloxacin prophylaxis reduced the occurrence of febrile episodes and deaths with a hazard ratio [HR] 0.66, (95% CI 0.51-0.86; p = 0.0018) when levofloxacin was delivered prophylactically compared to placebo.…”
Section: Improving Early Infection-related Morbidity and Mortality Mamentioning
confidence: 99%